The Factors Related to Breastfeeding in the Work Area of Bonto Biraeng Hamlet, Bonto Matene Village, Marusu District, Maros Regency - Fanni Astuti (Journal of Borneo Holistic Health, 2022)
Breastfeeding is the first natural food for babies which provides all the vitamins, minerals and nutrients a baby needs for growth in the first six months and no other food or fluids are needed. Breast milk fulfills half or more of a child's nutritional needs in the first year to the second year of life.The low level of breastfeeding in Indonesia is due to the lack of knowledge of pregnant women, families and communities about the importance of breastfeeding. This problem is exacerbated by the incessant promotion of formula milk and the lack of support from the community. This study aims to determine the factors associated with breastfeeding in Bonto Biraeng hamlet, Bonto Matene village, Marusu district, Maros Regency based on the variables of family support (husband), support from health workers and mother's motivation. This type of research is quantitative analytic with a cross-sectional approach and the total sampling method is using primary, secondary and questionnaire data.The results showed that there was a relationship between husband's support and breastfeeding, there was no relationship between the support of health workers and breastfeeding and there was a significant relationship between mother's motivation and breastfeeding..